Electrospun polyamide-6/chitosan nanofibers reinforced nano-hydroxyapatite/polyamide-6 composite bilayered membranes for guided bone regeneration. (15th May 2021) - Niu, Xiaolian; Wang, Longfei; Xu, Mengjie; Qin, Miao; Zhao, Liqin; Wei, Yan; Hu, Yinchun; Lian, Xiaojie; Liang, Ziwei; Chen, Song; Chen, Weiyi; Huang, Di
Graphical abstract: Highlights: Electrospun PA6/CS nanofiber reinforced n-HA/PA6 bilayered composite was designed. The composites are tightly bound and achieve seamlessly integrated layer structure. Tensile strength of composites is above 1.75 times than that of n-HA/PA6 scaffolds. Bilayered composite has biological safety, cytocompatibility and osteoconductivity. Abstract: Periodontal defect poses a significant challenge in orthopedics. Guided Bone Regeneration (GBR) membrane is considered as one of the most successful methods applied to reconstruct alveolar bone and then to achieve periodontal defect repair/regeneration. In this paper, a novel polyamide-6/chitosan@nano-hydroxyapatite/polyamide-6 (PA6/CS@n-HA/PA6) bilayered tissue guided membranes by combining a solvent casting and an electrospinning technique was designed. The developed PA6/CS@n-HA/PA6 composites were characterized by a series of tests. The results show that n-HA/PA6 and electrospun PA6/CS layers are tightly bound by molecular interaction and chemical bonding, which enhances the bonding strength between two distinct layers. The porosity and adsorption average pore diameter of the PA6/CS@n-HA/PA6 membranes are 36.90 % and 22.61 nm, respectively. The tensile strength and elastic modulus of PA6/CS@n-HA/PA6 composites are 1.41 ± 0.18 MPa and 7.15 ± 1.09 MPa, respectively. In vitro cell culture studies demonstrate that PA6/CS@n-HA/PA6 bilayered scaffolds have biological safety, good bioactivity, biocompatibility and osteoconductivity.